Smaller Audits : Challenges and Insights - Shukarova-Savovska, Kalina; Hodge, John (World Bank, Washington, DC, 2016)
Smaller audits are considered ‘a specialty’, with their own unique set of challenges for practitioners to address when engaging with smaller clients. This publication highlights some of those challenges and provides related insights that might be useful for practitioners, Small and Medium Sized Practices (SMPs) and Professional Accounting Organizations (PAOs) as they support their members.